'The Impossible Balancing Act': Reconstructing Liveness with NT Live's Hedda Gabler. (10th March 2020) - Zhou, Yangzi
Abstract: This article traces Ivo van Hove's Hedda Gabler from its staging by the National Theatre to its screening in China as a National Theatre Live production. I investigate how as a form of intermedial and international performance, NT Live alters the concept of 'liveness' between multiple frames of production and reception. During the delayed international transmission of NT Live, liveness is intertwined with the connections and variations between audience communities, making it an indicator of each experience's distinctive condition and locality rather than a proof of the reproduction and retainment of sameness. A case study of the National Theatre's Hedda Gabler from stage to screen and to China reveals that while van Hove's production constructs an intimate and exclusive community by strengthening the co-present corporeality of performers and spectators in theatre, the delayed screenings, in order to balance the loss of spatial and temporal liveness, employ culturally specific strategies to produce multiple mediatized, digitally 'live' experiences for new audience communities. By means of moulding theatre into technology-supported media, utilizing and negotiating with local audience's horizons of expectations as well as their feedback to the screened production, NT Live adapts the original performance and redefines liveness in exchange for an expanded outreach beyond national and cultural borders. It opens up and engages various audience communities whose participation sheds light on the cultural and political potentials and limitations of liveness in the age of digitalization and multimedia.